Trogolaphysa formosensis sp. nov. (Collembola: Paronellidae) from Atlantic Forest, Northeast Region of Brazil - Diego Dias da Silva; Bruno Cavalcante Bellini (Zoologia (Curitiba), 2015)
Trogolaphysa formosensis sp. nov. (holotype male deposited in DBEZ from Brazil, state of Rio Grande do Norte State, municipality of Bani Formosa), a new springtail from the Atlantic Forest domain, Rio Grande do Norte, Brazil, is described and illustrated. This species is diagnosed by unique coloration pattern, presence of 8+8 eyes, reduced number of setae on metatrochanteral organ, unguiculi truncated and dorsal chaetotaxy. Trogolaphysa formosensis sp. nov. is the first species of the genus from Brazil with all eye lenses. All other Brazilian species present 0+0 or 2+2 eyes. It is also the first species of Trogolaphysa described from the Northeast Region of Brazil.